2012
DOI: 10.1111/j.1538-7836.2012.04846.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive thrombocytosis and risk of subsequent venous thromboembolism: a cohort study

Abstract: Summary.  Background:  It is uncertain whether reactive thrombocytosis is associated with an increased risk of venous thromboembolism. This study assessed the incidence of reactive thrombocytosis, defined as platelet count ≥ 500 × 109 L−1, at intensive care unit discharge and its association with subsequent venous thromboembolism. Methods and Results:  This cohort study involved linkage of routinely collected intensive care unit, laboratory, radiology and death registry data of critically ill patients admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
52
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 32 publications
10
52
1
2
Order By: Relevance
“…Second, our results confirmed the increasing recognition of the importance of platelets and fibrinogen in the pathogenesis of critical bleeding, haemostasis and thrombosis (Duff et al, ; Ho et al, ; Hagemo et al, ). Our multivariate analysis results showed that fibrinogen concentrations and platelet counts certainly had a larger effect on in vitro clot strength than hypocalcaemia.…”
Section: Discussionsupporting
confidence: 88%
“…Second, our results confirmed the increasing recognition of the importance of platelets and fibrinogen in the pathogenesis of critical bleeding, haemostasis and thrombosis (Duff et al, ; Ho et al, ; Hagemo et al, ). Our multivariate analysis results showed that fibrinogen concentrations and platelet counts certainly had a larger effect on in vitro clot strength than hypocalcaemia.…”
Section: Discussionsupporting
confidence: 88%
“…Platelets play a central role in hemostasis and thrombosis [6], [7], but in accordance with our findings in the non-cancer cohort, the platelet count has not been associated with future risk of VTE in the general population [11][13]. Conversely, a significant association between reactive thrombocytosis and VTE has been confirmed in hospitalized medical patients [26], intensive care unit patients [27] and trauma patients [28], [29]. There is also growing evidence that platelet count is predictive of VTE in cancer patients.…”
Section: Discussionsupporting
confidence: 87%
“…Anemia, especially when caused by iron deficiency, can sometimes lead to thrombocytosis, which is a risk factor for venous thrombosis. 25,26 This mechanism would be in line with the fact that we observed a stronger association between CVT and microcytic anemia because iron deficiency is the most important cause of microcytic anemia. Unfortunately, thrombocytes were not measured in the MEGA study, and thus we could not examine whether the presence of thrombocytosis modified the association between anemia and CVT.…”
Section: Discussionsupporting
confidence: 81%